(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of fast food consumption and identify some related factors of fast food for students of Hanoi Medical University. Method: A cross-sectional descriptive study was conducted from September to December 2023 among 340 students at Hanoi Medical University. Data were collected through an online questionnaire using REDCap, covering fast food consumption habits and associated factors such as gender, residence, and income. Data were analyzed using STATA 15.0. Results: The proportion of students who frequently consumed fast food was 42.4%. Students with a monthly income below 3 million VND tended to consume fast food more frequently (52.5%) compared to those with higher incomes (29.2%). Male students had a higher rate of fast food consumption during main meals than females (38% vs. 24.6%). Female students tended to consume fast food during both main and snack meals more than males (38.3% vs. 23%). Takeaway was the most common mode of consumption (> 60%). Conclusion: Fast food consumption is prevalent among medical students at Hanoi Medical University, even among those aware of its negative health impacts. There is a need to strengthen nutrition education and health communication to help students adopt healthier eating habits amid their demanding study schedules.